An Analysis of the Impact of Moving the National Capital on Indonesia's Maritime Security: a Literature Review - Sahrul, Sahrul; Wiranto, Surya; Yusnaldi, Yusnaldi; Firmansyah, Firmansyah; Yusuf, Andi M. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Indonesian government has decided to move the National Capital (IKN) from Jakarta to East Kalimantan. This move is not without reason, but rather an effort from the government to carry out equitable development that does not only focus on the island of Java, but more than that to increase national competitiveness, and realize a more advanced and sustainable Indonesia in the future. This research aims to determine the impact of the move to East Kalimantan on Indonesia's maritime security and the challenges and opportunities that arise for Indonesia's maritime security due to the move. This research uses a library research method with a qualitative approach, data derived from a literature study, and exploration of various trusted references so that the results of the study are expected to answer how the impact of the relocation of the National Capital (IKN) on Indonesia's maritime security.